The Effectiveness Of Administering Turmeric And Tamarind Drink (Sinom) In Reducing The Intensity Of Primary Dysmenorrhea Pain In Adolescent Girls - Ize Listiana Dewi; Nila Widya Keswara (CV. AFDIFAL MAJU BERKAH, 2026)
Primary dysmenorrhea is a gynecological complaint frequently experienced by adolescent girls and can disrupt their learning activities and quality of life. One non-pharmacological therapy that is developing in the community is the consumption of turmeric and tamarind drinks (sinom), which contain natural anti-inflammatory and analgesic compounds. This study aims to analyze the effectiveness of turmeric and tamarind drinks (sinom) on reducing the intensity of primary dysmenorrhea pain in adolescent girls at SMAN 1 Krucil. The study used a pre-experimental design with a one-group pretest-posttest approach. The study sample consisted of 41 respondents selected using a purposive sampling technique according to inclusion and exclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS), then analyzed using the Wilcoxon Signed-Rank Test. The results showed that before the intervention, the majority of respondents experienced moderate pain (63.4%) and severe pain (19.5%). After administration of sinom, the majority of respondents were in the mild pain category (56.1%), and the proportion of severe pain decreased to 7.3%. The Wilcoxon test showed a Z value of -5.165 with a p-value <0.001, indicating a significant decrease in primary dysmenorrhea pain intensity after administration of the turmeric and tamarind drink (sinom). These findings indicate that sinom is effective as an alternative non-pharmacological therapy in reducing primary dysmenorrhea pain in adolescent girls and has the potential to be developed as a locally-based health intervention that is easily accessible and safe to use.